Magnetic to non-magnetic transition of Ce induced by volume in Ce(Pd, Ni) and electron concentration in Ce(Pd, Rh) - Kappler, J.P.; Beaurepaire, E.; Krill, G.; Godart, C.; Nieva, G.; Sereni, J.G.; Sereni, Julián; Nieva, Gladys (EDP Sciences, 1988)
Fil: Nieva, G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina